Neonatal 6-OHDA Lesion Model in Mouse Induces Cognitive Dysfunctions of Attention-Deficit/Hyperactivity Disorder (ADHD) During Young Age - Bouchatta, Otmane; Manouze, Houria; Ba-M’Hamed, Saadia; Landry, Marc; Bennis, Mohamed (Frontiers in Behavioral Neuroscience, 2020)
Attention-deficit/hyperactivity disorder (ADHD) is a syndrome characterized by impaired attention, impulsivity and hyperactivity in children. These symptoms are often maintained in adults. During adolescence, prefrontal cortex develops connectivity with other brain regions to engage executive functions such as, latent inhibition, attention and inhibitory control. In our previous work, we demonstrated the validity of the neonatal 6-Hydroxydopamine (6-OHDA) mouse model, a classical neurodevelopmental model mimicking major symptoms of the human ADHD pathology. In order to evaluate pathological forms of executive functions and impulsive behavior in 6-OHDA mice during young age, we first tested latent inhibition (LI) after weaning, and then we evaluated the impulsive behavior using a cliff avoidance reaction test. Our results demonstrated that 6-OHDA mice showed disruption in latent inhibition, suggesting a deficit in selective attention, and displayed repetitive peering-down behavior, indicating a maladaptive impulsive behavior. Subsequently, to assess impulsivity and attention in young mice, we performed a modified 5-choice serial reaction time task test (5-CSRTT), optimizing the degree of food restriction for young animals and shortening the training duration. This test allowed us to demonstrate a deficit in inhibitory control and a loss of accuracy of 6-OHDA mice in the 5-CSRTT. In conclusion, we demonstrated that the 6-OHDA mouse model reproduces human symptoms of ADHD in childhood and early adulthood periods, as seen in human. Taken together, the 6-OHDA mouse model will be useful alongside other animal models to understand the neurobiological mechanisms underlying complex, heterogeneous neurological disorders.